Risk factors for early local lymph node recurrence of thoracic ESCC after McKeown esophagectomy - Dai, Liang; Yang, Yong-Bo; Wu, Ya-Ya; Fu, Hao; Yan, Wan-Pu; Lin, Yao; Wang, Zi-Ming; Chen, Ke-Neng (Frontiers in Surgery, 2023)
Objectives: Even underwent radical resection, some patients of thoracic esophageal squamous cell carcinoma (ESCC) are still exposed to local recurrence in a short time. To this end, the present study sought to differentiate patient subgroups by assessing risk factors for postoperative early (within one year) local lymph node recurrence (PELLNR). Methods: ESCC patients were selected from a prospective database, and divided into high- and low-risk groups according to the time of their local lymphatic recurrence (within one year or later). Survival analysis was conducted by the Cox regression model to evaluate the overall survival (OS) between the two groups. The hazard ratio (HR) and 95% confidence interval (CI) of different variables were also calculated. Logistic regression analysis was used to explore the high-risk factors for PELLNR with the odds ratio (OR) and 95% CI calculated. Results: A total of 432 cases were included. The survival of patients in the high-risk group (n=47) was significantly inferior to the low-risk group (n=385) (HR=11.331, 95% CI: 6.870-16.688, P＜0.001). The 1-y, 3-y, and 5-y OS rate of the patients in high/low-risk groups were 74.5% vs. 100%, 17% vs. 88.8%, and 11.3% vs. 79.2%, respectively (P＜0.001). Risk factors for local lymph node recurrence within one year included upper thoracic location (OR=4.071, 95% CI: 1.499-11.055, P=0.006), advanced T staging (pT3-4, OR=3.258, 95% CI: 1.547-6.861, P=0.002), advanced N staging (pN2-3, OR=5.195, 95% CI: 2.269-11.894, P<0.001), and neoadjuvant treatment (OR=3.609, 95% CI: 1.716-7.589, P=0.001). In neoadjuvant therapy subgroup, high-risk group still had unfavorable survival (Log-rank P＜0.001). Multivariate analysis demonstrated that upper thoracic location (OR=5.064, 95% CI: 1.485-17.261, P=0.010) and advanced N staging (pN2-3) (OR=5.999, 95% CI: 1.986-18.115, P=0.001) were independent risk factors for early local lymphatic recurrence. However, the cT downstaging (OR=0.862, 95% CI: 0.241-3.086, P=0.819) and cN downstaging (OR=0.937, 95% CI: 0.372-2.360, P=0.890) for patients in the neoadjuvant subgroup failed to lower PELLNR. The predominant recurrence field type was single-field. Conclusions: Thoracic ESCC patients with lymph node recurrence within one year delivered poor outcomes, with advanced stages (pT3-4/pN2-3) and upper thoracic location considered risk factors for early recurrence.